2021
DOI: 10.1590/1983-21252021v34n311rc
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Substrate in the Protected Cultivation of Muskmelon

Abstract: Melon is a vegetable of great socioeconomic importance, and its cultivation is carried out under different production systems. The protected cultivation of melon can be carried out in coconut shell fiber, which is a substrate widely used in olericulture, but little information is available regarding its continuous use in more than one cultivation cycle. Therefore, this study aimed to evaluate the performance of muskmelon hybrids as a function of the reuse of coconut shell fiber with fertigation in a protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…The average values observed were 0.18 g 100 mL -1 between irrigation frequencies and 0.17 g 100 mL -1 between substrate volumes. These values are higher than those obtained by Vargas et al (2021), who observed titratable acidity of 0.11 g 100mL -1 of pulp of netted melon grown in a protected environment.…”
Section: Resultscontrasting
confidence: 74%
“…The average values observed were 0.18 g 100 mL -1 between irrigation frequencies and 0.17 g 100 mL -1 between substrate volumes. These values are higher than those obtained by Vargas et al (2021), who observed titratable acidity of 0.11 g 100mL -1 of pulp of netted melon grown in a protected environment.…”
Section: Resultscontrasting
confidence: 74%